Utilization of Dry Seaweed (DSWAC) for Removal of zinc ions (Zn²⁺) from Aqueous Solution - HGEIG, ALI; Ftes, Gamal; Althallouti, Ezdehar; Ben yahya, Karima (Sharwes Scientific Journal, 2026)
Dry seaweed (DSWAC) was utilized as a precursor for the preparation of activated carbon through chemical activation using phosphoric acid at 400 °C. The activation process was carried out with different impregnation ratios of (H₃PO₄/ Dry seaweed): 3:130%, 4:130%, 3:150%, and 4:150%. The effects of several key operational parameters, including contact time, initial metal ion concentration, adsorbent dosage and pH. The equilibrium data were analyzed using the Langmuir, Freundlich, and Temkin adsorption isotherm models, the Langmuir and Freundlich showed satisfactory correlation coefficients. According to the Langmuir model, the maximum adsorption capacity was determined to be 58.90 mg g⁻¹ at room temperature. The adsorption kinetics of zinc ions (Zn²⁺) were evaluated using pseudo-first-order, pseudo-second-order, and intraparticle diffusion models. Among these models, the pseudo-second-order model provided the best description of the kinetic data. Overall, the (DSWAC) adsorbent demonstrated significant potential for zinc ions (Zn²⁺) removal from aqueous solutions, highlighting its applicability as an environmentally friendly and low-cost adsorbent material.